An organisational cultivation of digital resignation?: Enterprise social media, privacy, and autonomy - Bagger Christoffer (Nordicom Review)
Enterprise social media (ESM) have largely gone ignored in discussions of the datafication practices of social media platforms. This article presents an initial step towards filling this research gap. My research question in this article regards how employees of companies using the ESM Workplace from Facebook feel that the implementation of this particular platform relates to their potential struggles for digital privacy and work–life segmentation. Methodologically, I explore this through a qualitative interview study of 21 Danish knowledge workers in different organisations using the ESM. The central analytical proposal of the article is that the interviewees express a “digital resignation” towards the implementation of the ESM. In contrast to previous discussions, this resignation cannot only be thought of as “corporately cultivated” by third parties, but must also be considered as “organisationally cultivated” by the organisations people work for. The study suggests that datafication-oriented media studies should consider organisational contexts.